Water pollution monitoring of the Lujan River (Argentina): Chemical analyses and hepatic biomarkers in Lithobates catesbeianus tadpoles - Ossana, Natalia Alejandra (2017)
The toxicological water quality of the Lujan River (Argentina) was monitored during one year seasonal samplings. Water samples were collected at two points and their toxicological profiles were compared: S1 (reference site), located downstream of a major city and S2, located further downstream, beyond a joint urban sewage and industrial discharge point. A number of abiotic parameters were determined and three water quality indices (WQIs) calculated on the samples. Laboratory toxicity bioassays were conducted exposing Lithobates catesbeianus larvae to samples; a third group of animals were exposed to tap water (controls). Hepatic biomarkers were determined: catalase (CAT), glutathione-S-transferase (GST) and superoxide dismutase (SOD) activities, lipid peroxidation (LPO) and GSH content; CF and HSI were calculated. The scores of the WQIs corresponded to a high pollution condition at both sampling points. ANOVA showed significant differences between sampling sites and controls mainly in CAT activity, GSH content and GST in autumn.